SCH 39304 in the treatment of acute or established murine pulmonary blastomycosis. - Brummer, E (1991)
SCH 39304 was tested for treatment of acute or established murine pulmonary blastomycosis and was compared with ketoconazole and fluconazole in a model of acute infection. Only SCH 39304 at 25 or 50 mg/kg of body weight per day produced 100% survival for 30 days after the 20-day treatment, although only 33% of the mice were cleared of infection. SCH 39304 at 2 mg/kg/day was similar to ketoconazole at 100 mg/kg/day and to fluconazole at 10 mg/kg/day. In a model of established blastomycosis, used to evaluate long-term treatment of very sick or moribund mice, SCH 39304 at 50 mg/kg/day protected against death with a 96% cumulative 8-week survival. SCH 39304 was clearly superior on a milligram-per-kilogram basis in acute blastomycosis, and long-term treatment of more severe blastomycosis was curative.